2005
DOI: 10.2225/vol8-issue2-fulltext-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature on the sorption of Pb2+ and Cd2+ from aqueous solution by Caladium bicolor (Wild Cocoyam) biomass

Abstract: This report is based on the investigation of the effect of temperature on the removal of Pb 2+ and Cd 2+ in aqueous effluent using C. bicolor biomass in a batch sorption process. The result showed that the most suitable sorption temperature was 40ºC with maximum sorption capacities of 49.02 mg/g and 52.63 mg/g for Pb 2+ and Cd 2+ respectively. Various thermodynamic parameters, such as ∆G o , ∆H o , ∆S o and E a have been calculated. The data showed that the sorption process is spontaneous and exothermic in na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
147
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 340 publications
(183 citation statements)
references
References 13 publications
(14 reference statements)
25
147
0
1
Order By: Relevance
“…According to the adsorption theory, adsorption decreases with increase in temperature and molecules adsorbed earlier tend to desorb from the surface at elevated temperature [17]. This was found to be true in the present study.…”
Section: E Effect Of Temperaturesupporting
confidence: 85%
“…According to the adsorption theory, adsorption decreases with increase in temperature and molecules adsorbed earlier tend to desorb from the surface at elevated temperature [17]. This was found to be true in the present study.…”
Section: E Effect Of Temperaturesupporting
confidence: 85%
“…(Table 5) indicate the spontaneous nature of adsorption of metal ion by the biomass and the likelihood of increased spontaneity of the process induced by increased temperature. It is of note that ∆G o up to -20 kJ/mol are consistent with electrostatic interaction between sorption sites and the metal ion (physical adsorption) while ∆G o values more negative than -40 kJ/mol involve charge sharing or transfer from the biomass surface to the metal ion to form a coordinate bond (chemical adsorption) 33 . The ∆G o values obtained in this study for both metal ions are < -20 kJ/mol, indicative that physical adsorption is the predominant mechanism in the sorption process.…”
Section: Thermodynamic Parametersmentioning
confidence: 73%
“…High temperatures tend to decrease the boundary layer thickness; the metal ions therefore had increased tendency to escape from the biomass surface to the solution phase. The decreased adsorption with increasing temperature also suggests weak adsorption interaction between biomass surface and the metal ion, which supports physiosorption [31]. Regression analysis showed that particle density and porosity of adsorbents are important parameters for good adsorption.…”
Section: Resultsmentioning
confidence: 60%